Sense of Belonging in Adolescents Whose Parents Divorce and Remarry - Revelya Destryna Sahari; Destryna Nainggolan; Melati; Sovitriana, Rilla (Asian Journal of Multidisciplinary Research, 2025)
This study aims to describe the sense of belonging to family in adolescents whose parents divorced and remarried. Parental divorce in adolescence is a significant event that impacts changes in a child's social and emotional life. During this time, adolescents go through various important transitions that affect the development of their identity. A sense of belonging is considered a key element in ensuring that teens feel accepted, valued, and supported in the family. This study involved four resource persons, namely two subjects of adolescent girls aged 18-20 years and two significant others. Data were obtained through in-depth interviews with subjects and significant others. The results of the study showed that there was a difference in adolescents' sense of belonging depending on the post-divorce parental relationship. Teens whose parents can reconcile and build healthy communication tend to feel more valued and more connected to their families, even after remarriage. In contrast, teens whose parents are unable to reconcile with divorce tend to feel isolated and have difficulty building strong relationships with their families. These findings emphasize the importance of the role of parents in supporting the emotional recovery process and the development of a sense of belonging in adolescents after divorce.